The Missing Link in Preconceptional Care: The Role of Comparative Effectiveness Research. - Salihu, Hamisu; Salinas, Abraham; Mogos, Mulubrhan (Maternal & Child Health Journal, 2013)
This paper discusses an important element that is missing from the existing algorithm of preconception care, namely, comparative effectiveness research (CER). To our knowledge, there has been limited assessment of the comparative effectiveness of diverse interventions that promote preconception health, conditions under which these are most effective, for which particular populations, and their comparative costs. CER can improve the decision making process for the funding, development, implementation, and evaluation of comprehensive preconception care programs, specifically by identifying the most effective interventions with acceptable costs to society. This paper will examine the framework behind preconception care and how the inclusion of comparative effectiveness research and evaluation into the existing algorithm of preconception care could foster improvement in maternal and child health. We discuss challenges and opportunities regarding the utilization of CER in the decision making process in preconception health, and finally, we provide recommendations for future directions.